Влияние надбандажной протечки на аэродинамику осерадиального диффузора выхлопного патрубка ЦНД паровой турбины при изменении противодавления - Юдин, Юрий Алексеевич; Субботович, Валерий Петрович; Лапузин, Александр Викторович; Юдин, Александр Юрьевич (НТУ "ХПИ", 2010)
For axially symmetrical model of diffuser, which characteristic for the exhaust manifold of the LPT power steam turbines, at the change of pressure on the diffuser exhaust are resulted. It is shown that on the certain modes which are related to the change of the backpressure, at supersonic velocity in the peripheral region of diffuser the unsteady processes are initiated.
Keywords: КПД; лопатки рабочие; радиальный надбандажный зазор; стационарные режимы течения; нестационарные режимы течения